A study on cultural industry competitiveness in Shanghai. - Wang, Zhongwei. (2008)
Conceive a model for evaluating the advantage and disadvantage of cultural industry development and current level of cultural industry competitiveness and find out influential factors for Shanghai cultural industry competitiveness.